Development of sodium acetate trihydrate-ethylene glycol composite phase change materials with enhanced thermophysical properties for thermal comfort and therapeutic applications - Rohitash Kumar (Nature Portfolio, 2017)
Abstract The heat packs using phase change materials (PCMs) are designed for possible applications such as body comfort and medical applications under adverse situations. The development and performance of such heat packs rely on thermophysical properties of PCMs such as latent heat, suitable heat releasing temperature, degree of supercooling, effective heat releasing time, crystallite size, stability against spontaneous nucleation in metastable supercooled liquid state and thermal stability during heating and cooling cycles. Such PCMs are rare and the available PCMs do not exhibit such properties simultaneously to meet the desired requirements. The present work reports a facile approach for the design and development of ethylene glycol (EG) and aqueous sodium acetate trihydrate (SAT) based composite phase change materials, showing these properties simultaneously. The addition of 2–3 wt% EG in aqueous SAT enhances the softness of SAT crystallites, its degree of supercooling and most importantly the effective heat releasing time by ~10% with respect to aqueous SAT material. In addition, the maximum heat releasing temperature of aqueous SAT has been tailored from 56.5 °C to 55 °C, 54.9 °C, 53.5 °C, 51.8 °C and 43.2 °C using 2%, 3%, 5%, 7% and 10 wt% EG respectively, making the aqueous SAT-EG composite PCMs suitable for desired thermal applications.